Meningkatkan Hasil Belajar Fisika Peserta Didik Di Kelas VIII SMP Swasta Gane Raya Kabupaten Halmahera Selatan dengan Model Pembelajaran Tipe Team Games Tournament (TGT) pada Materi Gelombang - atrisialin dodootor (Program Studi Pendidikan Fisika STKIP Kie Raha Ternate, 2023)
This Study aims to improve students’ physics learning outcomes in class VIII Gane Raya Private Middle School, South Halmahera Regency with the Team Games Tournament Cooperative Learning Model. The method used by researchers is a qualitative method, with 11 students. The data sources come from teachers and students. Researcher data collection techniques were carried out using observation sheets on the implementation of learning models and test questions. The data obtained were analyzed by descriptive qualitative. Based on the of class VIII action research at Gane Raya Private Middle School, South Halmahera Regency, it produced data, namely the result obtained in cycle I showed a result of 18,18 %. And in cycle II there was in increase in student learning outcomes of 90,9 %. This shows that there is an increase in learning outcomes by using the Team Games Tournament learning model for Class VIII of Gane Raya Private Middle School, South Halmahera Regency on wave material